Electromyographic analysis in elite swimmers with shoulder pain during a functional task - Sabzehparvar, E.; Khaiyat, O.A.; Namin, B. G.; Minoonejad, H. (Sports Biomechanics, 2021)
The purpose of study was to determine and compare electromyographic activity of selected shoulder girdle muscles in elite swimmers with and without shoulder pain. Twelve professional swimmers with shoulder pain (mean age: 18.55 ± 3.16 years, body mass: 74.33 ± 2.91 kg and height: 179.00 ± 5.29 cm) and 12 swimmers without pain (mean age: 18.11 ± 1.61 years, body weight: 73.33 ± 6.06 kg, height: 178.33 ± 5.07 cm) were recruited. Surface electromyography signals were collected from seven upper limb muscles during a task: participants were instructed to mark points with a pen within each of the three circles counterclockwise. The normalised root-mean-square value was used to determine the muscular activation. Swimmers with shoulder pain demonstrated greater activation of the upper trapezius (pain group mean: 28.04 ± 10.37, control group mean: 13.40 ± 06.04; p = 0.002, N2p: 0.455), serratus anterior (pain group mean: 30.78 ± 20.09, control group mean: 13.30 ± 5.52; p = 0.023, N2p: 0.283) and latissimus dorsi (pain group mean: 27.05 ± 17.87, control group mean: 4.99 ± 3.90; p = 0.002, N2p : 0.450) muscles. There was no difference (p > 0.05) in the activation of the middle and lower trapezius, middle deltoid and sternocleidomastoid. The altered muscle activation patterns may contribute to the painful shoulder in elite swimmers and need to be considered within the rehabilitation interventions.